If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+15-92=2(x+2)
We move all terms to the left:
3x+15-92-(2(x+2))=0
We add all the numbers together, and all the variables
3x-(2(x+2))-77=0
We calculate terms in parentheses: -(2(x+2)), so:We get rid of parentheses
2(x+2)
We multiply parentheses
2x+4
Back to the equation:
-(2x+4)
3x-2x-4-77=0
We add all the numbers together, and all the variables
x-81=0
We move all terms containing x to the left, all other terms to the right
x=81
| x+3x+2x+(x+1)=30 | | 0.8x+6=2.9-3x | | g/10=20 | | -10x+5=-6x-40 | | x+145=165=30+x | | 15.5x-14.3=10.5x+2.815.5x−14.3=10.5x+2.8 | | -13x+39+(-13x)+39=180 | | 100+35x=75+40x | | 3x+15-92=(x+2) | | 9+10n=69 | | 10-6+10x=2x-12+4x | | 5x+2-2-3x=9+5 | | -1(7x+4x-5)=9-(3x+5) | | -5x-30=7 | | 3/5(35x+15)=2/3(9x-21) | | 3/m+4=9 | | 3(x+1)-2(x+1)=2x+10 | | 0.5(x+20)=2+0.75(x−2) | | 6n=246 | | 8x=4=68 | | 1/6(12x-18)=2x=3 | | 16-4n=12 | | 8x+4=98 | | (5x+16)+90+100+102=180 | | Y=5.2(8-y) | | -2z-0z=-21 | | 6x−35+3x+35=180 | | 5t+5t=6-16 | | m/2+-4=-3 | | 2x+5+3x=4-(x-4) | | 12=3(d-14) | | 3v-(2.34)=9.57 |